2018
DOI: 10.1002/jcph.1116
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Intramuscular and Intravenous Ketamine in Children

Abstract: Ketamine is an N-methyl D-aspartate receptor antagonist used off-label to facilitate dissociative anesthesia in children undergoing invasive procedures. Available for both intravenous and intramuscular administration, ketamine is commonly used when vascular access is limited. Pharmacokinetic (PK) data in children are sparse, and the bioavailability of intramuscular ketamine in children is unknown. We performed 2 prospective PK studies of ketamine in children receiving either intramuscular or intravenous ketami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…In a larger population‐based modeling approach study, the reported bioavailability after i.m. administration in children was 41% 24 . This and our estimated value of ~ 64% reflects the current dosing recommendation of i.m.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In a larger population‐based modeling approach study, the reported bioavailability after i.m. administration in children was 41% 24 . This and our estimated value of ~ 64% reflects the current dosing recommendation of i.m.…”
Section: Discussionsupporting
confidence: 78%
“…This agrees with studies that reported a 2-compartment model to be the best fit for observed ketamine concentrations in both children and adults. [24][25][26][27] A previous study reported an absolute bioavailability of 93% after i.m. administration.…”
Section: Discussionmentioning
confidence: 99%
“…Study 27. Hornik et al 37 9 (2020) performed a pharmacokinetic analysis of earlier published data 10 on the influence of the nitric oxide donor sodium nitroprusside on S-ketamine and R,S-ketamine pharmacodynamics. In 20 volunteers both formulations were administered on separate occasions and the concentrations of R-and/or S-ketamine and metabolites (norketamine, dehydronorketamine, and hydroxynorketamine) were measured in arterial plasma.…”
Section: Perioperative Medicinementioning
confidence: 99%
“…Similar values were reported when the population pharmacokinetic data were pooled to racemic ketamine plasma concentrations collected in children with burns. A recent study reported similar estimates in 0.02‐ to 17.6‐year‐old children after the administration of a racemic mixture via IV and IM routes (elimination clearance, 38.9 L/hour/70 kg; steady‐state distribution volume 184.8 L/70 kg). ( S )‐Ketamine administration as a 3.6 mg/kg/hour intravenous infusion in 0.02‐ to 12.5‐year‐old children under intensive care showed faster clearance (112 L/hr/70 kg) and larger volume (552 L/70 kg) compared to the racemic mixture.…”
mentioning
confidence: 71%